SOFTWARE REUSE AND OBJECT ORIENTED APPROACH - Halil ŞENGONCA; Yasemin TOPALOĞLU; Oğuz DİKENELLİ (Pamukkale University Journal of Engineering Sciences, 1995)
Software reuse is defined as the reuse of information and products of a previously developed software system in the development process of a new software system. The purpose of software reuse is to reduce the development cost and the time, while increasing the software quality. Constructing a library of software components and using them in developing complex software systems was first proposed by Dough McIlroy in 1968. Since then programming languages, tools and techniques have changed a lot, but component oriented software reuse is still accepted as an important solution to solve the software crisis. Object oriented approach encourages component reuse, by inheritance and encapsulation. But in order to accomplish a succesful reuse program in an organization, a well-planned and coordinated managenment is essential. In this paper, an object oriented software development process is introduced and in order to instituionalize software reuse a strategy is proposed.